The relationship of office environment and employees' performance - Nadia Fatihah, Mastan. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study aims to examine the relationship of office enviroment and employees' performance among the academicians and support staffs in public institution of higher education and to identify the dominant factor that affects the employees' perfomance the most. The factors under investigation are comfort, interaction and distraction. A demographic factor of gender is also being tested to find out whether it has any significant differences towards performance. The study was conducted in UiTM Kota Samarahan, Saawak. Quantitative method using questionnaires were distributed to the respondents.